(untitled) (Journal of Telenursing (JOTING), 2023)
This research aims to determine the relationship between perceptions and community support for women with infertility. The research method uses quantitative descriptive analytical techniques with a cross-sectional approach. The research results show a relationship between perceptions and community support for women with infertility with a P value (0.000) < 0.05. In conclusion, the higher the public perception, the higher the public support. Keywords: Community support, infertility, perception